2012
DOI: 10.1093/ntr/nts217
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Weight Change in Sedentary Smokers Receiving a Standard Smoking Cessation Intervention

Abstract: Sedentary smokers receiving a standard smoking cessation intervention experience a moderate weight gain, limited to the first 3 months. Older age, male sex, and higher nicotine dependence are predictors of weight gain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 39 publications
(76 reference statements)
5
23
1
Order By: Relevance
“…On average, men gained 3.9 kg and women gained 3.3 kg 1 year after smoking cessation. High nicotine dependence was also associated with the greatest weight gain after cessation 56 . Furthermore, men experienced more weight gain during abstinence, which contradicts other studies 46,53 in which women experience more weight gain following cessation of smoking.…”
Section: Smoking Cessationmentioning
confidence: 90%
See 2 more Smart Citations
“…On average, men gained 3.9 kg and women gained 3.3 kg 1 year after smoking cessation. High nicotine dependence was also associated with the greatest weight gain after cessation 56 . Furthermore, men experienced more weight gain during abstinence, which contradicts other studies 46,53 in which women experience more weight gain following cessation of smoking.…”
Section: Smoking Cessationmentioning
confidence: 90%
“…Furthermore, men experienced more weight gain during abstinence, which contradicts other studies 46,53 in which women experience more weight gain following cessation of smoking. Older age (above the median age at entry of 43 years) was associated with continuing weight gain during relapse 56 . Overall, this study 56 suggests that older smokers, those who are men, and those with high nicotine dependence probably gain most weight after quitting smoking.…”
Section: Smoking Cessationmentioning
confidence: 96%
See 1 more Smart Citation
“…These results are discussed in details elsewhere [30]. Furthermore, the mean weight gain at one-year follow-up was also not significantly different in the two groups [31]. The full inclusion and exclusion criteria, as well as the study design and procedure are described in details elsewhere [30].…”
Section: Methodsmentioning
confidence: 99%
“…However, other investigations could not confirm this finding (Prod'hom et al, 2013;Allen et al, 2013). Similarly in our study, we found no association between being on active NRT (vs placebo) and changes in BMI post-quitting.…”
Section: Discussioncontrasting
confidence: 68%